Household archaeology in Ancient Israel and beyon d - Ebeling, Jennie R.; Mazow, Laura B.; Yasur-Landau, Assaf. (Culture and History of the Ancient Near East, 2011)
Despite the large number of well-preserved domestic contexts in Bronze and Iron Age sites, household archaeology has not been a common approach to studying the material culture of Ancient Israel. Until recently, the dictates of "Biblical Archaeology" led to a narrow set of questions that ignored issues such as gender, status and production within the household. The present volume, which grew out of a session at the 2008 Annual Meeting of the American Schools of Oriental Research, attempts to redress this issue. The seventeen papers herein reflect innovative viewpoints on the theory and praxis of household archaeology in this region. The next step in household research is presented here, with the use of tailor-made data collection strategies designed to answer specific questions posed by household archaeology. \'The neglect of households and the archaeology of the activities of its members are ambitiously attended to in this volume. Its exceptional breadth of various modes of inquiry coupled with the application thereof justifies the household as a topic of discussion. I would highly recommend this book for institutions, libraries, scholars, and students interested in any aspect of daily life in the southern Levant, and I very much look forward to the future research projects it will inspire.\' Cynthia Shafer-Elliot, William Jessup University \'...as a whole the work is impressive, and most contributions are commendable for their sophistication in engaging interdisciplinary research in order to understand the nature and function of households in ancient Israel and surrounding areas.\' Carol Meyers, Duke University